2023
DOI: 10.3390/healthcare11060782
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Rater and Inter-Rater Reliability Analysis of Muscle-Tone Evaluation Using a Myotonometer for Children with Developmental Disabilities

Abstract: Assessing muscle tone is an essential component of the diagnosis, prognosis, and treatment planning of developmental disabilities (DD) in children and is of great help in developing clinical diagnosis patterns. The purpose of this study was to investigate intra-rater and inter-rater reliability using the myotonometer, which is an assessment tool to measure muscle tone in children with DD. This study included 26 children diagnosed with DD. Two physical therapists measured the children’s muscle tone using a myot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…MyotonPRO has been used to evaluate mechanical properties in healthy individuals [12], athletes [13], and geriatric individuals [14], and various diseases [15,16]. However, in the pediatric group, myotonometric measurements are frequently preferred in diseases such as cerebral palsy, brachial plexus injury, and in children with developmental delays [17][18][19][20]. To date, no study has been found to investigate the changes in the viscoelastic properties of the lower-extremity muscles in pediatric hemophilia patients.…”
Section: Introductionmentioning
confidence: 99%
“…MyotonPRO has been used to evaluate mechanical properties in healthy individuals [12], athletes [13], and geriatric individuals [14], and various diseases [15,16]. However, in the pediatric group, myotonometric measurements are frequently preferred in diseases such as cerebral palsy, brachial plexus injury, and in children with developmental delays [17][18][19][20]. To date, no study has been found to investigate the changes in the viscoelastic properties of the lower-extremity muscles in pediatric hemophilia patients.…”
Section: Introductionmentioning
confidence: 99%